2020
DOI: 10.35848/1347-4065/ab8c9d
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of longitudinal leaky surface acoustic waves on LiNbO3/amorphous layer/quartz structure

Abstract: Recently, bonded structures comprising a quartz substrate and a LiNbO3 (LN) or LiTaO3 thin-plate have been attracting attention as a means of obtaining enhanced properties for surface acoustic wave (SAW) devices. It was reported that the bonding strength was extremely improved by utilizing an amorphous thin film as a middle layer. In this research, the propagation and resonance characteristics of longitudinal leaky SAWs on an amorphous layer inserted to the boundary between an X-cut 36°Y-propagating LN (X36°Y-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…As a result, it was found that a large K 2 and a small attenuation can be obtained when an X-cut thin plate of LT or LN is bonded to an X-cut quartz. 23,24) However, the plate thickness showing the minimum attenuation was about onethird of the plate thickness showing the maximum K 2 . Resolving this inconsistency is one of the current tasks of the author's research group.…”
Section: Lt or Ln Bonded To Quartz Substratementioning
confidence: 94%
See 2 more Smart Citations
“…As a result, it was found that a large K 2 and a small attenuation can be obtained when an X-cut thin plate of LT or LN is bonded to an X-cut quartz. 23,24) However, the plate thickness showing the minimum attenuation was about onethird of the plate thickness showing the maximum K 2 . Resolving this inconsistency is one of the current tasks of the author's research group.…”
Section: Lt or Ln Bonded To Quartz Substratementioning
confidence: 94%
“…1(d), a large K 2 , a small attenuation, and a small TCF can be obtained simultaneously for LSAW and LLSAW. [20][21][22][23][24] Some research groups have also investigated structures bonded to a quartz substrate. [25][26][27][28][29][30][31][32][33] In this section, recent results obtained by our group are presented.…”
Section: Lt or Ln Bonded To Quartz Substratementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many studies have been reported related to high-performance SAW devices. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The SAW propagation modes suitable for high-frequency devices include a shear horizontal (SH) leaky SAW (LSAW) and a longitudinal LSAW (LLSAW) with relatively high phase velocity. However, an LSAW has inherent attenuation because it propagates while radiating a shear vertical (SV) bulk wave into the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…LN is a popular piezoelectric material because of relatively high electromechanical coupling coefficient and high Curie temperature, around 1200 °C. [17][18][19][20][21] LN is used as single crystals and it is rare to use it as ceramics due to poling difficulty. In previous studies, Pb(Zr,Ti)O 3 (PZT) and Bi 4 Ti 3 O 12 (BiT) sol-gel solutions were used to produce LN/PZT 13,22,23) and LN/BiT 22,24) sol-gel composite ultrasonic transducers.…”
Section: Introductionmentioning
confidence: 99%